ISOLATION AND CHARACTERIZATION OF 3-METHYLCATECHOL SYNTHESIZED BY FUNGI FROM ANABASIS APHYLLA L. (Scientific journal of the Fergana State University, 2025)
This article describes the isolation and characterization of 3-methylcatechol synthesized by endophytes of the plant Anabasis aphylla L.. The endophytic fungi were cultured under favorable conditions for 14 days, followed by 14 days in unfavorable conditions, which stimulated the synthesis of secondary metabolites. The fungal culture liquid was extracted with ethyl acetate, and the resulting extract was separated by column chromatography, yielding an individual compound. The structure of the compound was studied using physicochemical methods, and the structure of 3-methylcatechol was determined as a result of the research.